2020
DOI: 10.1021/jacs.9b13027
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Reduction of Aryl Halides by a Photoexcited Perylene Diimide Radical Anion

Abstract: The ability of the doublet excited state of perylene diimide anion radical 2(PDI–•)* to reduce aromatic electron acceptors was probed by picosecond time-resolved transient absorption (TA) spectroscopy. Excitation of PDI–• produces visible TA due to 2(PDI–•)* that decays with τ = 160 ps. Aromatic electron acceptors with varying reduction potential quench 2(PDI–•)* and, in some cases, give a new visible region absorption that is attributed to the products of bimolecular photoinduced electron transfer, 2(PDI–•)* … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 25 publications
5
136
0
1
Order By: Relevance
“…A very recent picosecond‐transient‐absorption study provides direct evidence for the bimolecular electron transfer between photoexcited PDI .− and a range of substrates with reduction potentials more positive than −1.7 V vs. SCE . However, for substrates with more negative potentials (and this is likely the case for several of the initially investigated aryl chlorides), a different mechanism, possibly a thermally activated pathway, seems to be operative …”
Section: The Next Level: Reductive Excited‐state Quenching Followed Bmentioning
confidence: 99%
“…A very recent picosecond‐transient‐absorption study provides direct evidence for the bimolecular electron transfer between photoexcited PDI .− and a range of substrates with reduction potentials more positive than −1.7 V vs. SCE . However, for substrates with more negative potentials (and this is likely the case for several of the initially investigated aryl chlorides), a different mechanism, possibly a thermally activated pathway, seems to be operative …”
Section: The Next Level: Reductive Excited‐state Quenching Followed Bmentioning
confidence: 99%
“…Conversely, Zhang, Schanze, and co-workers have recently reported the use of picosecond time-resolved transient absorption spectroscopy to monitor the formation of A * À * and its bimolecular quenching by aryl halides 1 through Stern-Volmer studies. [33] The authors found that A * À * underwent efficient PET with electron-poor halides 1 having reduction potential > À 1.7 V vs SCE. Besides, they calculated the potential for the couple A * À */A as À 1.87 V vs SCE.…”
Section: Mechanistic Discussion: Reduction Of Aryl Halidesmentioning
confidence: 99%
“…Eine aktuelle Studie zur transienten Pikosekunden‐Absorption lieferte direkte Belege für bimolekulare Elektronentransferreaktionen zwischen angeregtem PDI .− und einer Auswahl an Substraten mit Reduktionspotentialen, die positiver als −1.7 V gegen SCE sind . Für Substrate mit negativeren Potentialen (und das ist wahrscheinlich der Fall für einige der anfänglich untersuchten Arylchloride) scheint hingegen ein anderer Mechanismus abzulaufen, möglicherweise ein thermisch aktivierter Reaktionsweg …”
Section: Die Nächste Ebene: Reduktives Löschen Angeregter Zustände Gunclassified